2013
DOI: 10.3390/ijms140816111
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Effects of Enriched Environment and Social Isolation in Ischemic Retinal Lesion in Adult Rats

Abstract: Exposure to an enriched environment has been shown to have many positive effects on brain structure and function. Numerous studies have proven that enriched environment can reduce the lesion induced by toxic and traumatic injuries. Impoverished environment, on the other hand, can have deleterious effects on the outcome of neuronal injuries. We have previously shown that enriched conditions have protective effects in retinal injury in newborn rats. It is well-known that the efficacy of neuroprotective strategie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 60 publications
0
10
0
1
Order By: Relevance
“…Environmental enrichment is a widespread neuroprotective strategy also in the mature nervous system. Our research group has shown that it can act as a protective factor against several types of harmful stimuli, like postnatal monosodium-glutamate toxicity [ 27 ], as well as neonatal and adult retina lesions [ 28 , 29 ]. In the last decade, impressive results have been obtained on the effects of enriched conditions in neurodegenerative diseases, such as Huntington’s disease, Alzheimer’s disease, amyotrophic lateral sclerosis, and Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Environmental enrichment is a widespread neuroprotective strategy also in the mature nervous system. Our research group has shown that it can act as a protective factor against several types of harmful stimuli, like postnatal monosodium-glutamate toxicity [ 27 ], as well as neonatal and adult retina lesions [ 28 , 29 ]. In the last decade, impressive results have been obtained on the effects of enriched conditions in neurodegenerative diseases, such as Huntington’s disease, Alzheimer’s disease, amyotrophic lateral sclerosis, and Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…Although the adult retina has long been considered less plastic than the brain cortex or hippocampus (the main loci of experience-dependent plasticity), a marked upregulation of the nerve growth factor induced gene-A and the activity-regulated cytoskeletal protein, two candidate-plasticity genes, was described in adult rats that had been exposed to an EE for 3 weeks [17]. Moreover, we have recently demonstrated that EE housing after retinal ischemia significantly protects retinal function and histology from ischemia/reperfusion injury in adult rats [18], and a recent study has confirmed that the outcome of retinal ischemia is improved by enriched housing in adult rats [19], supporting that environmental stimuli can significantly modify the extent of retinal damage in adult rats. In this context, the aim of this work was to analyze the effect of EE housing on retinal damage induced by early experimental diabetes.…”
Section: Introductionmentioning
confidence: 80%
“…Earlier studies have shown that the effects of EE overall generally appeared to be greater for males than for females 58 . For example, females are less responsive to the positive effects of EE and more vulnerable to retinal ischemia in social isolation 59 . Since gender differences have been implicated as a major variable of the response to the effect of drugs of abuse and treatment outcomes 60 61 62 , it would be necessary to investigate the effect of EE in female rats in the future.…”
Section: Discussionmentioning
confidence: 99%